Electrical and Electro-Optical Biosensors - Lee, Mon-Juan; Kim, Seunghyun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Electrical and electro-optical biosensing technologies are critical to the development of innovative POCT devices, which can be used by both professional and untrained personnel for the provision of necessary health information within a short time for medical decisions to be determined, being especially important in an era of global pandemics. This Special Issue includes a few pioneering works concerning biosensors utilizing electrochemical impedance, localized surface plasmon resonance, and the bioelectricity of sensing materials in which the amount of analyte is pertinent to the signal response. The presented results demonstrate the potential of these label-free biosensing approaches in the detection of disease-related small-molecule metabolites, proteins, and whole-cell entities.